Application of electronic diaries in patients with schizophrenia and bipolar disorders - Mutschler, Jochen; Großhans, Martin (Psychiatria danubina, 2012)
Background: Despite the dissemination of second generation antipsychotics for schizophrenia and bipolar disorder, outcomes remain suboptimal, largely due to poor treatment and drug adherence. The primary aim of the current study was to assess the tolerability, validity and feasibility of the pocket-sized electronic diary Medicus®. Subjects and methods: Our case observations attempted to evaluate eighteen patients suffering from schizophrenia and bipolar disorder. All of the patients were treated with the second generation antipsychotic quetiapine. We followed them up in two German medical centers over two years. Results: The present results display an improvement of mood-stability in all patients treated with quetiapine. All patients were in regular contact to their psychiatrist over a period of 24 months. A complete description of the coherences between the symptoms was essential for estimation, which was conducted by Medicus®. Moreover, Medicus® seem to be useful for improving compliance within a medication regimen. Conclusions: Although uncontrolled case observations can only be interpreted with caution, Medicus® seems to deserve further investigation and may hold the potential to optimize treatment and drug adherence in patients suffering from schizophrenia and bipolar disorders.